PENGARUH MEDIA PENETASAN TERHADAP KEMAMPUAN TETAS DAN DAYA HIDUP JANGKRIK (Gryllus testaceus) - Alina, Dewi; Lusi Z, S.Si, M.Si, Armein; Kasmeri, S.Si, M.Si., Ria (STKIP PGRI Sumbar, 2014)
ABSTRACTMedia hatchery of crickets egg require to be paid attention in crickets conducting, because in this media is crickets will be incubated. If the media less good hence ability hatchery it also lessgood so it also with energy of crickets live. In crickets conducting, breeders not yet recognized other medias to incubated crickets egg. The purpose of this research is to know influence of hatch media to ability hatchery and energy live cicada and also to know best hatchery media for the hatchery of crickets egg andÂ energy live of crickets. This research done in Korong Gadang kecamatan Kuranji, Padang, in January 2014. Method that used in this research was random devicecomplete with 5 treatment that was A: river sand media, B: Coastal sand media, C: hay media, D:dustyâs kitchen media, and E: cotton media. Each repeated until 5 times restart. The materials used in this research was 250 crickets egg item, where each treatment filled by 10 crickets egg. The data got would be analysis by varianse later, then if there a difference will test to continue with level95%. The result of this research indicated that media have an effect of reality (P>0,05) to ability hatch and energy live of crickets. Percentage of ability hatch cricket egg and energy life highest of crickets there were at treatment of river sand media that is equal 66% and hay media to 81%. It ca be concluded from the result of this research that hatch media have an effect on reality to ability hatch and energy live of crickets. Media which suite for process hatch of crickets child that was river sand and hay media.Â